Respon Kutu Putih Pepaya dan Tanaman Pepaya terhadap Aplikasi Asam Salisilat: english - octriana, Liza; Putra, Nugroho Susetya; Suputa, Suputa (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2019)
Salicylic acid is one of the elicitor substances that can be used to reduce the level of damage of plants, both by pathogen and herbivore. The application of salicylic acid also affects plant growth and productivity. The impact of the salicylic acid application on a plant varies, such as depending on concentration, mode of application, and plant species. This research aimed to know the effect of different salicylic acid concentrations on mealybug development and papaya growth. The results showed that salicylic acid at concentrations of 100 mg/l slowed mealybug development and suppressed the amount of fecundity. Still, it caused a plant to grow smaller relatively. The application of salicylic acid at a concentration of 50 mg/l was the best treatment because it provided the best growth of papaya plants and suppressed the fecundity of mealybug.